Analysis of Character Education Values in Rangku Alu Dance for Dance Learning in Elementary School - Resti Yulianti,; Non Dwishiera Cahya Anasta, (International Conference on Elementary Education, 2025)
Globalization currently causes an increase in individualism among students, which impacts the decline of character and social concern. Dance learning can serve as a medium for strengthening character education because it involves values such as discipline, cooperation, and creativity. However, in practice, dance learning often focuses solely on skill transfer, without involving comprehensive character development. The research uses qualitative methods with a case study approach, aiming to identify character values in the rangku alu dance, explore its application, and examine the obstacles that arise. The research results show that the rangku alu dance contains character values such as perseverance, cooperation, discipline, courage, and appreciation of culture. These values are applied through structured learning strategies, such as scaffolding to build confidence, group work to enhance cooperation, a consistent practice schedule to build discipline, providing motivation to encourage students, and appreciating local culture through understanding the meaning of the dance. The obstacles encountered include low student motivation and confidence, as well as time constraints in dance learning. In conclusion, the rangku alu dance is not only a part of art education but also a strategic medium for instilling character values, making it an effective tool to support students' character education.